2017
DOI: 10.1111/ctr.13114
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing risks and benefits of living kidney donors with a history of thyroid cancer

Abstract: Many potential and willing living kidney donors are excluded from donating for a history of malignancy. There is appropriate caution toward patients with a history of malignancy because of concern for transmission of donor-derived malignancy. Thyroid cancer is common and increasing in incidence, and outcomes are very good in otherwise young, healthy potential donors. We review the evidence and guidelines regarding recurrence and transmission risk of thyroid cancer, and then we suggest a standardized guideline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(53 reference statements)
1
3
0
Order By: Relevance
“…Although transplantation from a donor with neoplasia constitutes a minority (5%), it produces a valuable increase in organs to transplant with a reasonable value of safety. Reviewing the literature we found that rate of malignancy detection in the various cohorts varies from 0.3 to 9% [3,[5][6][7][8], and type of neoplasm affecting donors are similar to other studies [6][7][8][9][10][11][12], whilst transmission of malignancy occurs in a very small subset.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although transplantation from a donor with neoplasia constitutes a minority (5%), it produces a valuable increase in organs to transplant with a reasonable value of safety. Reviewing the literature we found that rate of malignancy detection in the various cohorts varies from 0.3 to 9% [3,[5][6][7][8], and type of neoplasm affecting donors are similar to other studies [6][7][8][9][10][11][12], whilst transmission of malignancy occurs in a very small subset.…”
Section: Discussionsupporting
confidence: 82%
“…It is proposed that current guidelines for the use of organs from donors with malignancy are revised, as the graft and patient survival was no different to standard risk donors [3], including high risk CNS tumors [10,16,17]. A recent paper suggests that living donors with a history of thyroid carcinoma should be considered as potentially suitable donors [11]. There is a documented high risk of transmission of melanoma and most of evidence still supports a strong contra-indication, given the relatively relevant number of cases of transmission [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Such decisions are often made on a case-by-case basis. 19,20 Several large published transplantation series found that hematological neoplasms and melanoma, lung, and breast cancer have the greatest risk of transmission. [21][22][23] To the best of our knowledge, only 1 case was reported in which metastatic follicular thyroid carcinoma was transmitted with a transplanted kidney.…”
Section: Discussionmentioning
confidence: 99%
“…An important issue is the limited time available to complete donor evaluation, in order not to delay organ recovery. As a general rule, 19,20 potential donors typically undergo US-guided examination of their thyroid gland, while blood tests (thyroid stimulating hormone and calcitonin) are ordered upon request. When a newly discovered thyroid nodule needs further investigation, there are no clear protocols to follow.…”
Section: Discussionmentioning
confidence: 99%